Simple QED- and QCD-like models at fnite density - Pawlowski, Jan M.; Stamatescu, Ion-Olimpiu; Zielinski, Christian (Arxiv, 2015)
In this paper we discuss one-dimensional models reproducing some features of quantum electrodynamics and quantum chromodynamics at nonzero density and temperature. Since a severe sign problem makes a numerical treatment of QED and QCD at high density difficult, such models help to explore various effects peculiar to the full theory. Studying them gives insights into the large density behavior of the Polyakov loop by taking both bosonic and fermionic degrees of freedom into account, although in one dimension only the implementation of a global gauge symmetry is possible. For these models we evaluate the respective partition functions and discuss several observables as well as the Silver Blaze phenomenon.
Gesehen am 30.11.2017